VALIDITY AND PRACTICALITY OF THE PROJECT MODULE: INTEGRATING PARAMASAN DAYAK LOCAL WISDOM - Wardhani, Dyah Febria; Arisanty, Deasy; Nugroho, Agung; Utami, Umi Baroroh Lili (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2024)
This study evaluates the validity and practicality of the developed The Pancasila Student Profile Strengthening Project module, designed to support the implementation of the Pancasila Student Profile. The module's validity was assessed across three key aspects: presentation, content, and language, achieving an average score of 93.75%, which classifies it as